Blessings or burdens : an interpretative phenomenological analysis (IPA) study on the motivations and their impact on end-of-life caregiving among Asian family caregivers - Tan-Ho, Geraldine (2020)
Background: While the impact of family caregiving has been well-documented, many of such studies center on investigating external factors such as socioeconomic status, accessibility to resources and availability of social support as the primary causation of caregiver wellbeing outcomes. This paper explores the motivations that drive family caregivers in supporting their family members at the end-of-life, and critically examines how internal appraisal processes of such motivations can both positively and negatively impact their wellbeing. Methods: This study adopted an interpretative phenomenological analysis (IPA) to investigate the motivations and internal appraisal processes of Asian family caregivers in Singapore who were tending to a dying family member. Qualitative dyadic interview data (N = 20) was drawn from a larger Randomized Controlled Trial for a novel Family Dignity Intervention (FDI) for palliative care patients and their families. The sampling population consisted of participants aged 21 and above who were identified to be the primary caregivers of older palliative care patients with a prognosis of less than 12 months. Data collection was conducted in the homes of patients and family caregivers. Results: Findings revealed six themes that could either nurture or diminish caregiver wellbeing: 1) Honoring Fidelity (caregivers were motivated to commit to their caregiving roles in order to avoid regret), 2) Alleviating Suffering (caregivers were motivated to relieve their family member’s pain), 3) Enduring Attachment (caregivers were motivated to spend time together with their family member), 4) Preserving Gratitude (caregivers were motivated to express their appreciation to their family member by caregiving), 5) Navigating Change (caregivers were motivated to adapt accordingly to changes in the illness trajectory) and 6) Reconciling with Mortality (caregivers were motivated to respond accordingly to their family member’s prognosis). The final theme of the Wellbeing Determinant is posited as an indication of self-determination, and is conjectured to influence how caregiving motivations are appraised by the caregiver. Conclusion: Fulfilling and enhancing one’s sense of self-determination appears central to infusing one’s caregiving motivations with positive meaning, and consequently nurturing one’s wellbeing in the end-of-life caregiving journey. These findings are discussed with recommendations for healthcare professionals working with family caregivers of palliative care patients.